The Comparison Results of Logit and Probit Regression on Factors of Woman Criminal - Nisa, Eva Khoirun; Muanalifah, Any (Universitas Muhammadiyah Mataram, 2021)
Logit and probit regression are statistical methods that have the same is to determine predictor variables affect the categorical response variable. From relevant studies, they have advantages and disadvantages on certain cases. Therefore, the logit and probit regression will be applied on factors of woman criminal considering women crime rate in Central Java is still relatively high. This study aims to compare the result of the two regression so that the best regression model is obtained to explain factors that influence woman criminal. The data type used is primary data obtained using a questionnaire and validated by non-empirical validation. The sample was taken using a quota sampling technique. The result showed that probit regression is the best model with the factors that influence woman criminal are the age of 17-25 years, 26-35 years, junior high school education level, married and ever married marital status.